Islamization of communication theory - Hussain, Mohd Yusof (Routledge, 1986)
The 1970s is looked upon as the period marking the revival of Islam. Islam places high priority on communication and the Quran gives strict guidelines to Muslim religious communicators on the do’s and don’t that have to be adhered to. The principles of communication laid down by Prophet Muhammad are discussed before the author discusses Western Communication Theories that can be effectively Islamized.